Dynamic Metabolic Changes in the Human Thalamus at the Transition From Waking to Sleep - Insights From Simultaneous Functional MR Spectroscopy and Polysomnography - Lehmann, Mick; Hock, Andreas; Zoelch, Niklaus; Landolt, Hans-Peter; Seifritz, Erich (Frontiers in Neuroscience, 2019)
An important contribution of the thalamus to the transition from wakefulness to sleep is a consistent finding in animal studies. In humans, only little is currently known about the specific role of the thalamus in regulating wake-sleep transitions. Although changes in thalamic blood flow and activity have been reported, the underlying molecular mechanisms have not been investigated. Knowledge about neurotransmitter changes at the wake-to-sleep transition would be indispensable for a better translation of basic animal research findings to humans. Here, we start to fill this important scientific gap. More specifically, we benefit from recent advances in magnetic resonance spectroscopy (MRS), which allow for the non-invasive, local-specific and high-quality detection of naturally occurring metabolite changes in the human brain. We demonstrate in 9 young adults able to produce consolidated sleep in the MRS scanner a specific decrease in thalamic glutamate concentration from wakefulness to N2 sleep (t = 3.74, p < 0.01). The magnitude of this decrease was highly correlated with individual N2 sleep duration (r = 0.84, p = 0.005). When 5 participants were kept awake in a separate control condition, no decrease in thalamic glutamate levels occurred. The study highlights for the first time in humans that dynamic changes in distinct brain metabolites can be reliably detected at the transition from waking to sleep. The reported methodology to simultaneously acquire MRS and neurophysiological signals offers great potential for investigating the molecular mechanisms underlying the gating and maintenance of sleep and wake in humans.